Humanistic logic of civil self-determination of global socium (Journal of Philosophy Culture and Political Science, 2018)
In the article integral reconstruction of genesis of civil forces of modern socium is presented. Life of humanity is presented as realization of humanistic logic of public progress is in the methods of joint activity of people. Motion of history is conditioned by spiritual priorities of public practice, aimed at rallying of people in socium, transformation of nature and comprehensive development of personality and voicing feel, reason and reason of the folk masses. Development of humanistic aims of public life determines the features of global epochs of history of humanity, related to the ideological options of «naturalistic humanism», «contemplative», «active» and «creative». Humanistic character of modern «innovative socium» is determined by successive cultivation in activity of the still human masses of civil values of «equality», «freedom» and «fraternity». Social quality of civil society is presented by intelligentsia as ideological enlightened class, aimed at every kind distribution of knowledge in society, on achievement of public benefit creative energy of scientific intellect «global socium» Formed now becomes firmly established in the productive specific as «educational society». Humanistic prospects of Russian society in XXI century will be determined by ideological potential of home scientifically-philosophical idea. Key words: humanism, historicism, global socium, civil society, educational society, civil personality.